Global proteomics and pathway analysis of pressure-overload-induced heart failure and its attenuation by mitochondrial-targeted peptides - Dai, Dao-Fu; Hsieh, Edward J; Chen, Tony; Menendez, Lorena G; Basisty, Nathan B; Tsai, Lauren; Beyer, Richard P; Crispin, David A; Shulman, Nicholas J; Szeto, Hazel H; Tian, Rong; MacCoss, Michael J; et al. (Circulation. Heart failure, 2013)
We investigated the protective effects of mitochondrial-targeted antioxidant and protective peptides, Szeto-Schiller (SS) 31 and SS20, on cardiac function, proteomic remodeling, and signaling pathways. We applied an improved label-free shotgun proteomics approach to evaluate the global proteomics changes in transverse aortic constriction (TAC)-induced heart failure and the associated signaling pathway changes using ingenuity pathway analysis. We found that 538 proteins significantly changed after TAC, which mapped to 53 pathways. The top pathways were in the categories of actin cytoskeleton, mitochondrial function, intermediate metabolism, glycolysis/gluconeogenesis, and citrate cycle. Concomitant treatment with SS31 ameliorated the congestive heart failure phenotypes and mitochondrial damage induced by TAC, in parallel with global attenuation of mitochondrial proteome changes, with an average of 84% protection of mitochondrial and 69% of nonmitochondrial protein changes. This included significant amelioration of all the ingenuity pathway analysis noted above. SS20 had only modest effects on heart failure and this tracked with only partial attenuation of global proteomics changes; furthermore, actin cytoskeleton pathways were significantly protected in SS20, whereas mitochondrial and metabolic pathways essentially were not. This study elucidates the signaling pathways significantly changed in pressure-overload-induced heart failure. The global attenuation of TAC-induced proteomic alterations by the mitochondrial-targeted peptide SS31 suggests that perturbed mitochondrial function may be an upstream signal to many of the pathway alterations in TAC and supports the potential clinical application of mitochondrial-targeted peptide drugs for the treatment heart failure.